From DREAM to REALITI‐A and beyond: Mepolizumab for the treatment of eosinophil‐driven diseases. Issue 3 (16th September 2021) - Pavord, Ian D.; Bel, Elisabeth H.; Bourdin, Arnaud; Chan, Robert; Han, Joseph K.; Keene, Oliver N.; Liu, Mark C.; Martin, Neil; Papi, Alberto; Roufosse, Florence; Steinfeld, Jonathan; Wechsler, Michael E.; et al.
Abstract: Effective treatment of inflammatory diseases is often challenging owing to their heterogeneous pathophysiology. Understanding of the underlying disease mechanisms is improving and it is now clear that eosinophils play a complex pathophysiological role in a broad range of type 2 inflammatory diseases. Standard of care for these conditions often still includes oral corticosteroids (OCS) and/or cytotoxic immune therapies, which are associated with debilitating side effects. Selective, biological eosinophil‐reducing agents provide treatment options that improve clinical symptoms associated with eosinophilic inflammation and reduce OCS use. Mepolizumab is a humanized monoclonal antibody that binds to and neutralizes interleukin‐5, the major cytokine involved in eosinophil proliferation, activation, and survival. Mepolizumab is approved for the treatment of severe eosinophilic asthma, eosinophilic granulomatosis with polyangiitis and hypereosinophilic syndrome. Additionally, the efficacy of add‐on mepolizumab has been observed in patients with severe chronic rhinosinusitis with nasal polyposis and chronic obstructive pulmonary disease with an eosinophilic phenotype. Here, we review the development, approval, and real‐world effectiveness of mepolizumab for the treatment of patients with severe eosinophilic asthma, from the DREAM to REALITI‐A studies, and describe how knowledge from this journey extended to the use of mepolizumab and other biologics across a broad spectrum of eosinophilic diseases.